The role of sea-level rise, monsoonal discharge and the palaeo-landscape in the early Holocene evolution of the Pearl River delta, southern China - Zong, Yongqiang (2013)
The early Holocene history of the Pearl River delta is reconstructed based on a series of sediment cores obtained from one of the main palaeo-valleys in the basin. Sedimentary and microfossil diatom analyses combined with radiocarbon dating provide new evidence for the interactions between sea-level rise, antecedent topography and sedimentary discharge changes within the deltaic basin since the last glacial. These new records show that river channels of last glacial age incised down to c. −40 m into an older (possibly MIS5 age) marine sequence which forms the floor of the deltaic basin and exists primarily at c. 10 m–15 m below present mean sea level. Rapid postglacial sea-level rise flooded the incised valleys by the beginning of the Holocene, and prior to c. 9000 cal. years BP, marine inundation was largely confined within these incised valleys. The confined available accommodation space of the incised valleys combined with strong monsoon-driven freshwater, high sediment discharge and a period of rapid rising sea level meant that sedimentation rates were exceptionally high. Towards c. 8000 cal. years BP as sea level rose to about −5 m, marine inundation spilled out of the incised valleys and the sea flooded the whole deltaic basin. As a result, the mouth of the Pearl River was forced to retreat to the apex of the deltaic basin, water salinity within the basin increased markedly as the previously confined system dispersed across the basin, and the sedimentation changed from fluvial dominated to tidal dominated. Sea level continued to rise, albeit at a much reduced rate between 8000 and 7000 cal. years BP, and deltaic sedimentation was concentrated around the apex area of the basin. During the last 7000 cal. years BP, the delta shoreline moved seawards, and the sedimentary processes changed gradually from tidal dominated to fluvial dominated.